Qur'anic Foundations of Digital Adab: A Thematic Exegesis and Its Implications for Islamic Religious Education in the Digital Age - Muhammad Iqbal; Oktari Kanus (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
The rapid expansion of digital technology has significantly transformed communication, learning, and social interaction, while simultaneously generating ethical challenges among young people, including misinformation, cyberbullying, hate speech, privacy violations, and irresponsible online behavior. Despite the growing importance of digital ethics, existing Islamic Religious Education practices tend to emphasize cognitive and doctrinal aspects of religion while providing limited guidance for navigating ethical challenges in digital environments. This study aims to examine the Qur'anic foundations of digital adab through thematic exegesis (tafsir maudhu'i) and to analyze their implications for Islamic Religious Education in the digital age. Employing a qualitative library research design, the study analyzes selected Qur'anic verses and contemporary literature on digital ethics, digital citizenship, and Islamic education using thematic content analysis. The findings identify five interconnected dimensions of Qur'anic digital adab: tabayyun (information verification), qaulan sadidan (truthful communication), qaulan layyinan (respectful and compassionate interaction), protection of human dignity and privacy, and digital responsibility and ethical accountability. The study reveals that these values provide a comprehensive ethical framework capable of addressing contemporary digital challenges while fostering responsible online participation and moral character development. The findings further demonstrate that the influence of these Qur'anic principles extends beyond personal morality and offers practical guidance for cultivating ethical digital citizenship among Muslim learners. The novelty of this study lies in the development of an integrated conceptual framework of Qur'anic digital adab that synthesizes classical Islamic ethical teachings with contemporary digital ethics and character education. This study contributes theoretically by enriching the emerging discourse on Islamic digital ethics and contributes practically by providing a framework for integrating digital adab into Islamic Religious Education curricula, digital literacy programs, and character education initiatives aimed at preparing ethically responsible Muslim digital citizens in the twenty-first century.